Analisa Laju Korosi Pada Plat Baja ASME SA-283 Pada Daerah Splash Zone - Reza Putra; Muhammad Muhammad; Abdul Rahman; M. Rifai Adithia (Jurnal Mekanova: Mekanikal, Inovasi dan Teknologi, 2020)
Research on the corrosion rate of ASME SA-283 alloy steel has been carried out in the coastal environment. Corrosion is a decrease in the quality of the material that occurs due to the environment, where the coast is a splash zone area which is rich in salt content as a trigger for corrosion. Alloy steel is a material that is used widely as part of the construction of dock buildings on the coast The study was carried out by giving coating defects to ASME SA-283 material and varying the salinity in the splash zone area, where the coating thickness ranged from 350 μm - 410 μm and salt splash testing was carried out for 15 days. The results of the salt splash test show the types of corrosion that occur, namely pitting corrosion and unifrom corrosion. The largest corrosion rate occurred in the area that experienced a coating defect of 1,705 mm / year. The effect of coating on the corrosion rate is very large and the effect of coating defects on corrosion growth is quite high because the coating that functions as a protective specimen has been lost. The aim of this study are expected to become a reference for coating protection data in preventing corrosion growth in coastal environments. Keywords— Coating Defects, Corrosion Rate, Splash zone, Salinity.